PEMETAAN BASIS DATA RELASIONAL MENJADI BASIS DATA RDF UNTUK SISTEM PEREKOMENDASI KOLEKSI PERPUSTAKAAN - Aditya Budi Utomo; Khamidudin Azzakiy; Hendrik Hendrik (Faculty of Industrial Technology Universitas Islam Indonesia, 2014)
In order to develop a library recommender system based on Semantic Web technology, it is a must to exploit the use of RDF model database. In this paper we explain our experiences in converting library inforation system’s data from relational database (RDB) into RDF model database. We achieve it by using an open source tool, D2RQ. We test the RDF database by querying the data using SPARQL. The result showing that we can use this tool easily to obtain our objectives.